2016
DOI: 10.1007/s00408-016-9876-1
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the Stem Cell Marker Gene CD133 and the Risk of Lung Cancer in Chinese Population

Abstract: These findings suggest that SNP rs2240688 A > C of CD133 may be a potential biomarker for genetic susceptibility to lung cancer, but require further research with larger populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…In contrast, previous studies of rs187116 variation reported that patients with at least one G allele, had an increased risk and recurrence of cancer after gastric surgery in Iran, Japan, North America, and Northeast Thailand (Winder et al, 2011;Bitaraf et al, 2015;Suenaga et al, 2015;Tongtawee et al, 2017). Our study of CD133, rs22406882 (c.*667A>C) shows that the C allele tended to increase the risk of cancer (OR: 1.46; 95% CI: 1.03-2.07; p = 0.033), which is consistent with previous reports that the AC or CC genotypes were associated with increased risk and reduced overall survival rate in lung cancer patients in China (Liu et al, 2016;. However, the variant AC/CC genotypes were associated with decreased risk of gastric cancer (OR: 0.81; 95% CI: 0.67-0.97; p = 0.023) (Jia et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, previous studies of rs187116 variation reported that patients with at least one G allele, had an increased risk and recurrence of cancer after gastric surgery in Iran, Japan, North America, and Northeast Thailand (Winder et al, 2011;Bitaraf et al, 2015;Suenaga et al, 2015;Tongtawee et al, 2017). Our study of CD133, rs22406882 (c.*667A>C) shows that the C allele tended to increase the risk of cancer (OR: 1.46; 95% CI: 1.03-2.07; p = 0.033), which is consistent with previous reports that the AC or CC genotypes were associated with increased risk and reduced overall survival rate in lung cancer patients in China (Liu et al, 2016;. However, the variant AC/CC genotypes were associated with decreased risk of gastric cancer (OR: 0.81; 95% CI: 0.67-0.97; p = 0.023) (Jia et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that the tumor suppressor gene (FOXO3) and proto-oncogene (MDM2) are involved in evading growth suppressors, and the apoptotic genes (caspase 8 and caspase 9) relate to resisting cell death. Moreover, the variation of cancer stem cell marker genes (CD44 rs187116, CD44 rs13347, CD44 rs4756196, CD133 rs3130, CD133 rs2240688, and ALDH1A1), were reported to be associated with an increasing cancer risk (Winder et al, 2011;Jiang et al, 2012;Liu et al, 2016;Lin et al, 2018). The results of this study showed that CD44 rs187116 and CD133 rs2240688 of cancer stem cell marker genes, the inflammatory gene, NF-κB1, and the detoxification gene, GSTM1 were significantly associated with an increased risk of breast cancer (p = 0.041, p = 0.033, p = 0.046, and p = 0.005, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified a number of cellular markers which include CD133 (38)(39)(40) and CXCR4 (41,42), that may contribute to the properties exhibited by lung CSCs. Chemokines are a family of small secreted proteins of ~70-80 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells group harboring in tissues of patients with NSCLC were detected by using markers of either ALDH1 or CD133, as were reported and applied before. [28][29][30][31][32][33][34][35] Higher ratios of both ALDH1C cells ( Fig. 1A) and CD133C (Fig.…”
Section: Ratios Of Cancer Stem Cells In Nsclc Correlates With Prognosismentioning
confidence: 99%